The Power of Emotions at Work - McLaren, Karla (Ascent Audio, 2021)
We've all been taught that we must suppress or avoid emotions at work, but this inevitably leads to a loss in productivity, diminished creativity, and crushing job dissatisfaction. Research shows eighty-five percent of us avoid communicating crucial workplace problems upward, and many of us who are employed are actively looking for a different job. What's going on? "The foundational problem is that we threw emotions out of the workplace, when in fact, emotions contain the information we need to make our workplaces work," says Karla McLaren. Now this renowned researcher shares her insights on the skills we most need-and are most often absent in the business world-for healthy, functional, and sustainable workplaces. With The Power of Emotions at Work, McLaren teaches communication and empathy skills to workers at all levels, including: how to co-create a healthy and well-balanced social environment that benefits all workers in any type of organization; how to recognize your primary emotional role-and the roles of others; how to support people in your organization who perform the most "emotional labor"; where to find authentic motivation and engagement in your job; how to go from an "unintentional community" to a place of genuine belonging; and much more.